ADRENOCORTICAL SYSTEM HORMONES IN NON-CRITICALLY ILL COVID-19 PATIENTS - (:unkn) unknown (EDITURA ACAD ROMANE, 2022)
Context. The effects of COVID-19 on the adrenocortical system and its hormones are not well known. Objectives. We studied serum cortisol, serum adrenocorticotropic hormone (ACTH), and their ratio in hospitalized non-critically ill COVID-19 patients. Design. A prospective case-control study. Methods. The study participants were divided into 2 groups. Group 1 consisted of 74 COVID-19 patients. The second group consisted of 33 healthy persons. Early admission above hormones levels was determined and compared between the study groups. Besides that, COVID-19 patients were grouped according to their Glasgow Coma Score (GCS), CURB-65 score, and intensive care unit (ICU) requirement, and further sub-analyses were performed. Results. There were no significant differences in the mean age or gender distribution in both groups. In the patients' group, the serum ACTH concentration was lower than in the healthy group (p<0.05). On the other hand, the serum cortisol levels and cortisol/ACTH ratio of the patients' group were significantly higher than of the healthy controls (p<0.05, all). Further analyses showed that, although serum cortisol and ACTH levels were not high, the cortisol/ACTH ratio was higher in COVID-19 patients with low GCS (<15) than patients with normal GCS (=15) (p<0.05). In COVID-19 in patients with different CURB-65 scores, the cortisol/ACTH ratio was significantly different (p<0.05), while serum cortisol and ACTH were not different in groups (p>0.05). Serum cortisol levels and cortisol/ACTH ratio were higher but ACTH level was lower in the ICU needed COVID-19 patients than in patients who do not need ICU (p<0.05). Conclusion. Our pilot study results showed that the cortisol/ACTH ratio would be more useful than serum cortisol and/or ACTH levels alone in evaluating the adrenocortical system of COVID-19 patients. Still, further detailed studies are needed to confirm these.
Keywords: COVID-19; cortisol; ACTH; CURB-65; coronavirus; pandemic; CORTISOL CONCENTRATIONS; MORTALITY; RATIO